The impact of National Death Index linkages on population-based cancer survival rates in the United States - Johnson, Christopher J. (Cancer Epidemiol, 2012)
BACKGROUND: In order to ensure accurate survival estimates, population-based cancer registries must ascertain all, or nearly all, patients diagnosed with cancer in their catchment area, and obtain complete follow-up information on all deaths that occurred among registered cancer patients. In the US, linkage with state death records may not be sufficient to ascertain all deaths. Since 1979, all state vital statistics offices have reported their death certificate information to the National Death Index (NDI). OBJECTIVE: This study was designed to measure the impact of linkage with the NDI on population-based relative and cancer cause-specific survival rates in the US. METHODS: Central cancer registry records for patients diagnosed 1993–1995 from California, Colorado, and Idaho were linked with death certificate information (deaths 1993–2004) from their individual state vital statistics offices and with the NDI. Two databases were created: one contained incident records with deceased patients linked only to state death records and the second database contained incident records with deceased patients linked to both state death records and the NDI. Survival estimates and 95% confidence intervals from each database were compared by state and primary site category. RESULTS: At 60 months follow-up, 42.1–48.1% of incident records linked with state death records and an additional 0.7–3.4% of records linked with the NDI. Survival point estimates from the analysis without NDI were not contained within the corresponding 95% CIs from the NDI augmented analysis for all sites combined and colorectal, pancreas, lung and bronchus, breast, prostate, non-Hodgkin lymphoma, and Kaposi sarcoma cases in all 3 states using relative survival methods. Additional combinations of state and primary site had significant survival estimate differences, which differed by method (relative versus cause-specific survival). CONCLUSION: To ensure accurate population-based cancer survival rates, linkage with the National Death Index to ascertain out of state and late registered deaths is a necessary process for US central cancer registries.